Integral cross sections for elastic electron scattering by methane molecule. Issue 18 (January 2020) - Maljković, J B; Vuković, J; Tökési, K; Predojević, B; Marinković, B P
Synopsis: We have performed a combined experimental and theoretical study of electron elastic differential and integral cross sections from methane molecule (CH4) in the intermediate energy range. Data have been compared with available data sets in the literature as well as with recommended data set [Song et al J. Phys. Chem. Ref.Data 44 023101 (2015)].